Transformasi Bentuk Arsitektur Rumah Godang Pada Perancangan Museum Jalur Kuantan Singingi - Gushendri Gushendri; Wahyu Hidayat; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Museum Jalur Kuantan Singingi is a special museum that only contains a collections of historical and cultural heritage of Kuantan Singingi District. Museum Jalur Kuantan Singingi design uses the geometric form transformation concept and primary concern is the inside space and outside space concept of the museum. The inside space and outside space concept of the museum using geometric transformations, combination of architecture Rumah Godang concept and pacu jalur. The concept of space in the museum using the imaginary space concept available on the Rumah Godang. The facades of buildings and outdoor spaces using the combination of the geometric form transformation concept of Rumah Godang and the geometric form of pacu jalur, that’s transforming elements of Rumah Godang to the building design at Museum Jalur Kuantan Singingi. The elements are the roof, wall, window,door, ladder and pole. While the geometric form of pacu jalur shown on the diagonal poles like as paddle-shaped of jalur.Keywords: Museum, Form Transformation, Rumah Godang of Kuantan Singingi, Pacu Jalur.